APPLICATION OF ZERO WASTE TECHNOLOGY IN SOLID WASTE OF SHRIMP TAMBAK IN SRIMINOSARI VILLAGE, LABUAN MARINGGAI, LAMPUNG TIMUR - Andi Setiawan Setiawan; Ni Luh Gede Ratna Juliasih (Jurnal Pengabdian Kepada Masyarakat Sakai Sambayan, 2021)
The application of zero waste technology in the handling of pond sludge is an alternative solution that can be done to overcome the problem of decreasing the productivity of shrimp ponds.This activity aims to provide guidance to shrimp farmers in the Sriminosari Village to apply zero waste technology in handling solid waste and processing it into a planting medium. The method of activity is carried out through technical approaches and guidance in the field. The activity target is a group of productive partners in the Sriminosari village. Partner groups gain an understanding of zero waste technology through guidance both theoretically and practically in the field. This activity was attended by 10 participants consisting of shrimp pond owners, Karang Taruna, and representatives from UKM Pemuda Sriminosari. The evaluation results show a very significant increase in understanding the concepts of zero waste (theoretically) in participants. Through technical guidance, a tool of a suction sludge with a capacity of 200 m3 per minute was successfully designed and equipped with 10 drums of sludge filter. Furthermore, the sludge waste has also been successfully processed into a media for planting. Based on the results, it can be concluded that there is an increase in the ability of partners in terms of implementing zero waste technology in handling solid waste in shrimp ponds. In addition, there is a new business opportunities related to shrimp pond maintenance services and businesses based on processing solid waste in shrimp ponds.